The future of crime and punishment: smart policies for reducing crime and saving money - Kelly, William R. (Rowman & Littlefield, 2016)
Acknowledgments -- Introduction -- American criminal justice : the punishment is the crime -- The high cost of failure -- Why people commit crime and what we can do about it -- Diversion from traditional criminal prosecution and punishment -- Changing prosecution and sentencing -- Rethinking punishment -- Drugs, guns and gangs -- Juvenile justice : the critical opportunity -- Conclusions -- References -- Index